Manajemen Pengembangan Sumber Daya Manusia dalam Meningkatkan Kompetensi Kepribadian Guru di Madrasah Aliyah Hidayatul Mubtadiin Lampung Selatan - Milatun Nangimah; Nurul Hidayati Murtafiah; Nur Widiastuti (Journal on Education, 2023)
This research aims to find out Management of Human Resource Development in Improving Teacher Personality Competence at Madrasah Aliyah Hidayatul Mubtadiin Sidoharjo Village, Jati Agung District, South Lampung Regency. This type of research is descriptive qualitative research. The method used in this study is to use the method of observation, interviews, and documentation. The data analysis technique used is an interactive model and data triangulation to check the validity of the data. Based on the results of this study, it can be concluded that 1. Planning for Human Resource Development in Improving Teacher Personality Competence, namely by holding a deliberation meeting which is carried out at the new school year or at the beginning of the semester with the involvement of related parties, namely the Head of Madrasah, Deputy Head of Curriculum, Deputy Head of Student Affairs, Council of Teachers , and all educational staff. 2. The Program for Implementing Human Resource Development in Improving Teacher Personality Competence in Madrasah Aliyah Hidayatul Mubtadiin Based on the decision of the Madrasah head, there are 6 Activities for Implementing the Human Resource Development Program in Improving Teacher Personality Competence which are routine and incidental, namely: Dzuhur Prayer in Congregation, Apples Morning, Islamic Studies, MGMP, Motivation Training, Religious Tour or Walisongo Pilgrimage. 3. Evaluation of the Human Resource Development Management program in Improving Teacher Personal Competence at Madrasah Aliyah Hidayatul Mubtadiin is carried out in the form of monitoring and supervision from the Madrasah head to Teachers and teacher attitude assessment carried out by students by voting or voting to obtain and obtain The title as the best and most favorite teacher will be announced at the commemoration of National Teacher's Day, which is on November 25.